Modelling of insulation in DC systems: the challenges for HVDC cables and accessories - Vu Thi Thu Nga; Gilbert Teyssedre (Vietnam Journal of Science, Technology and Engineering, 2020)
Cable technologies have evolved in different ways for applications using high voltage alternating current (HVAC) and high voltage direct current (HVDC) over the last 40 years. Since the 1950s, mass-impregnated paper was progressively replaced by extruded insulation made of polyethylene and then crosslinked polyethylene (XLPE). The switch from paper insulation to extruded cables went on continuously while cables were designed with ever increasing voltage requirements. However, regarding space charge build-up and field redistribution, particularly at polarity reversal stages in thyristors, the behaviour of extruded cables under such DC stress is not fully understood. For this reason, material improvement, characterization, and modelling are still intensively researched for cables, accessories, and power conversion equipment. The weaknesses and methods used to simulate the characteristics of insulation are presented and compared in this work through the simulation results of the macroscopic and fluid model.